Tumor Necrosis Factor Receptor 1/c-Jun-NH(2)-Kinase Signaling Promotes Human Neoplasia - Zhang, Jennifer Y. (2007)
The tumor necrosis factor α receptor (TNFR1) activates downstream effectors that include the mitogen-activated protein kinase kinase 7 (MKK7)/c-Jun-NH(2)-kinase (JNK)/activator protein 1 (AP1) cascade. Here, we report that JNK is activated in a majority of spontaneous human squamous cell carcinomas (SCC). JNK pathway induction bypassed cell cycle restraints induced by oncogenic Ras and cooperated with Ras to convert normal human epidermis into tumors indistinguishable from SCC, confirming its oncogenic potency in human tissue. Inhibiting MKK7, JNK, and AP1 as well as TNFR1 itself using genetic, pharmacologic, or antibody-mediated approaches abolished invasive human epidermal neoplasia in a tumor cell autonomous fashion. The TNFR1/MKK7/JNK/AP1 cascade thus promotes human neoplasia and represents a potential therapeutic target for human epithelial cancers.